Diagnostic value of biomarkers in multiple sclerosis - Zafranskaya, Marina M. (Journal of the Belarusian State University. Ecology, 2019)
Multiple sclerosis (MS) is a classic neuroinflammatory disease involving the aberrant balance of T-, B- and myeloid cells (including microglia), which are potential targets for the manifestation of biomarkers. Presently, based on prospective randomized clinical trials, genetic and cell biomarkers allowing adequately disclosing / assessing all aspects of the immune system damage due to MS and to personalize the selective immunotherapy taking into account the inflammatory status, cellular and humoral sensitization of a patient have been validated. However, additional studies are required to implement the obtained results into clinical practice. Biomarkers are objective indicators of physiological and pathological processes; in clinical settings, they can be used as a diagnostic, prognostic and therapeutic tool. In MS, the identification of definite biomarkers may be of exceptional interest for developing specific prognostic methods to predict therapeutic efficacy and personalize the treatment protocol.
Keywords: biomarkers; multiple sclerosis; personification